PPARG2 Pro12Ala and TNFα -308G>A Polymorphisms Are Not Associated with Heart Failure Development in Patients with Ischemic Heart Disease after Coronary Artery Bypass Grafting. (2nd June 2019) - Wojtkowska, Izabela; Bonda, Tomasz A.; Tysarowski, Andrzej; Seliga, Katarzyna; Siedlecki, Janusz A.; Winnicka, Maria M.; Stępińska, Janina
Abstract : TNF α and PPAR γ are important modulators of metabolism, inflammation, and atherosclerosis. Coronary artery disease is the leading cause of heart failure (HF). The aim of the study was to assess whether polymorphisms of the TNFα (-308G>A) and PPARG2 (Pro12Ala) genes are associated with the risk of developing HF by patients with ischemic heart disease. Methods . 122 patients without HF (aged 63 ± 8.8 years, 85% males) with confirmed coronary artery disease qualified for coronary bypass grafting were enrolled in the study. After the procedure, they were screened for cardiac parameters. Those with elevated NT-proBNP or diminished left ventricular ejection fraction during follow-up were assigned to the HF group (n=78), and the remaining ones to the non-HF group (n=44). The TNFα -308G>A and PPARG 2 Pro12Ala polymorphisms were detected using the TaqMan method. Results . The distributions of TNFα -308G>A and PPARG 2 Pro12Ala did not differ between the HF and non-HF groups (-308G>A: 16% vs. 11.4% of alleles; Pro12Ala: 23.9% vs. 20.5% of alleles, respectively). IL-6 concentration in the plasma of TNFα A-allele carriers at months 1 and 12 after CABG was higher in the HF group compared to the non-HF group (1 month after CABG: 5.3 ± 3.4 vs. 3.1 ± 2.9, p<0.05; 12 months after CABG: 4.2 ± 3, 9 vs. 1.4 ± 1.2, p<0.01, respectively). Both polymorphisms were not related to changes in the plasma TNF α concentration or other parameters related to HF. Conclusions . Our study did not reveal any correlation between the PPARG2 Pro12Ala and TNFα -308G>A polymorphisms and development of HF in patients with ischemic heart disease after coronary bypass grafting.